Evaluating the Impact of Primary Care Consultations on Teenage Lifestyle: A Pilot Study - Walker, Z. A. K.; Oakley, L. L.; Townsend, J. L. (Methods of Information in Medicine, 2000)
This study piloted an evaluation of the effectiveness of inviting teenagers to UK general practice consultations with health behaviour advice and appropriate follow-up care. 132 teenagers aged 14/15 years were randomised: intervention teenagers were invited to attend a health consultation with a practice nurse, the control group received usual care. Teenagers in two practices were consulted by postal survey and in focus groups to ensure the intervention met their needs. 56% of the teenagers invited attended for a consultation. 55% of the intervention group and 45% of the controls reported some positive change in health related behaviour at one month.
Keywords: Family Practice; Health Promotion; Adolescent Health Services; Adolescence; Randomised Controlled Trial